Dengue Mosaic Vaccines Enhance Cellular Immunity and Expand the Breadth of Neutralizing Antibody Against All Four Serotypes of Dengue Viruses in Mice - Hou, Jue; Shrivastava, Shubham; Fraser, Christopher C.; Loo, Hooi Linn; Wong, Lan Hiong; Ho, Victor; Fink, Katja; Ooi, Eng Eong; Chen, Jianzhu (Frontiers in Immunology, 2019)
An estimated 400 million people in the world are infected with any of the four types of dengue virus (DENV) annually. The only licensed dengue vaccine cannot effectively prevent infection with all of the four DENVs, especially in those immunologically naïve at baseline. In this study, we explored a mosaic vaccine approach, which utilizes an artificial recombinant sequence for each serotype to achieve maximum coverage of variant epitopes in the four DENVs. We determined the immunogenicity and cross-reactivity of DNA plasmids encoding individual mosaic sequences or the natural sequences in mice. We show that the mosaic vaccines, particularly those targeting DENV serotype 1 and 2, improved vaccine immunogenicity by increasing the percentage of antigen-specific IFNγ- or TNFα-secreting CD4 and CD8 T cells and titers of neutralizing antibodies. The mosaic vaccine diversified and broadened anti-dengue T cell responses and cross-reactive neutralizing antibodies against all four serotypes. The mosaic vaccines also induced higher level of antigen-specific B cell responses. These results suggest that mosaic vaccines comprising of DENV serotype 1 and 2 variant epitopes could stimulate strong and broad immune responses against all four serotypes.